Pilot mental health sensitisation programme for community leaders in Uganda: impact evaluation - Shuttleworth, Linda;; Pontin, Francesca (Cambridge University Press, 2025)
Despite worldwide uptake, there has been little published evaluation of actually delivering the World Health Organization (WHO) Mental Health Gap Action Programme (mhGAP) in typical low- and middle-income countries (LMICs). This paper aims to evaluate the impact of a pilot study in which mhGAP guidelines for mental health sensitisation of community leaders were implemented in 1-day training events across 25 urban and rural health facilities ( n = 1004 community leaders) in Uganda. A multiple choice mental health questionnaire was used to assess the community leaders’ mental health knowledge before and after completing the training. Training was evaluated across multiple sites and qualitative feedback comments were used to identify key themes on the impact of the training. The sensitisation training was found to be affordable, accessible and effective, and could be replicated in other LMICs and settings with local adaptations. CrossRef
Keywords: . Low- and middleincome countries; mental health services; impact evaluation; mhGAP; community leader sensitisation.